Knowledge, attitudes and practices of COVID-19 infection prevention and control among nurses in the intensive care unit at Groote Schuur Hospital, Cape Town - Onga, Bangani (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.